Direct and indirect connections of androgen status with ejaculate parameters in men from infertile couples - E. A. Epanchintseva; V. G. Selyatitskaya (Сибирский научный медицинский журнал, 2024)
In men from infertile couples the serum level of total testosterone (tT) has been shown to vary widely. Is it possible to expect that there is an association of tT content with spermogram disorders in men from infertile couples? Aim of the study was to investigate the patterns of changes in the spermiological status of men from infertile couples depending on tT level in blood serum. Material and methods. Design – observational, retrospective, one-stage study. The analysis of medical histories of 358 men with infertility in marriage was carried out. The sample was divided into comparison groups according to tT level: group 1 – less than 12.1, group 2 – from 12.1 to 20.9, group 3 – 21.0 nmol/l or more. Results. From group 1 to group 3, tT content increases more than twice, as well as concentration of indicators related to the level of T – sex hormone binding globulin (SHBG) and free testosterone (fT). There are no significant differences in luteinizing hormone (LH) and follicle stimulating hormone (FSH) level, although there is a tendency to its increase from group 1 to group 3. From group 1 of men with androgen deficiency to group 3, not only body weight and body mass index (BMI), but also waist circumference (WC) and hip circumference (HC), as well as the WC/HC index, characterizing the degree of abdominal obesity, decrease. The groups examined did not differ in the values of all studied ejaculate parameters. In group 1, a pronounced correlation between the content of tT and fT was found, in groups 2 and 3 – statistically significant inverse relationships between the level of Tob and the values of anthropometric indicators (body weight, BMI, WC and HC), as well as direct ones - with the concentration of SHBG, tT, LH and estradiol, in group 3 – with FSH levels. There were no correlations between tT content and spermogram indicators in any group of examined men. Conclusions. The results obtained suggest that only at high-normal level of testosterone in the blood it can have a stimulating effect on spermatogenesis. As a result of the accumulation of cases of androgenic deficiency in the population, the direct positive effect of serum testosterone on spermatogenesis is becomes insufficient for normal regulation, and the negative effect of testosterone deficiency on spermatogenesis, mediated through the accumulation of overweight and obesity comes to the fore.